Relaciones competitivas entre Proechimys Semispinosus y Hoplomys Gymnurus (Rodentia: Echimyidae) en el occidente colombiano - Alberico Michael; González M. Alonso (Caldasia, 1993)
Comparative data about movements, density, home range, and reproductive activity of Proechimys semispinosus and Hoplomys gymnurus (Rodentia: Echimyidae) were obtained by means of an eight-month capture-recapture study in the Bajo Calima region of the pacific coast of Colombia. In addition, intra and interespecific behavioral interactions were studied in captivity. Hoplomys gymnurus had a higher density than Proechimys semispinosus in the primary forest habitat, while the reverse situation was found in the secondary forest. The behavior of Proechimys semispinosuswas more agresive than that of Hoplomys gymnurus. In interespecific encounters, individuals of the former species showed a marked dominance and the latter always showed a submissive behavior.We propose that interference competition is minimized by means of microhabitat selection; Hoplomys gymnurus occurs preferentialiy in primary forest and Proechimys semispinosus in secondary forest in this region. Por medio de un estudio ecológico de marcaje y recaptura durante ocho meses, en la zona de Bajo Calima en la costa pacífica de Colombia, se obtuvieron datos sobre movimientos, rango vital, densidad y actividad reproductiva de Proechimys semispinosus y Hoplomys gymnurus (Rodentia: Echimyidae). Adicionalmente, se hicieron observaciones sobre el comportamiento intra e interespecífico en condiciones de cautiverio. En el bosque primario, la densidad de Hoplomys gymnurus fue superior a la de Proechimys semispinosus, mientras que en el bosque secundario, se encontró la situación opuesta. En su comportamiento la segunda especie fue más agresiva que la primera. En encuentros interespecíficos, sus individuos se caracterizaron por una marcada dominancia y los de Hoplomys gymnurus siempre terminaron exhibiendo un comportamiento sumiso. Se propone que la competencia por encuentros se reduce mediante la selección del microhábitat; Hoplomys gymnurus ocupa preferencialmenteel bosque primario y Proechimys semispinosus el bosque secundario.